The Energetics of Mangrove Forests - Alongi, Daniel M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2009)
Despite their importance in sustaining livelihoods for many people living along some of the world's most populous coastlines, tropical mangrove forests are disappearing at an alarming rate. Occupying a crucial place between land and sea, these tidal ecosystems provide a valuable ecological and economic resource as important nursery grounds and breeding sites for many organisms, and as a renewable source of wood and traditional foods and medicines. Perhaps most importantly, they are accumulation sites for sediment, contaminants, carbon and nutrients, and offer significant protection against coastal erosion. This book presents a functional overview of mangrove forest ecosystems; how they live and grow at the edge of tropical seas, how they play a critical role along most of the world's tropical coasts, and how their future might look in a world affected by climate change. Such a process-oriented approach is necessary in order to further understand the role of these dynamic forests in ecosystem function, and as a first step towards developing adequate strategies for their conservation and sustainable use and management. The book will provide a valuable resource for researchers in mangrove ecology as well as reference for resource managers.
From the content 1. Introduction -- 2. Trees and Canopies. 2.1 Introduction. 2.2 Biomass Allocation. 2.3 Ecophysiology. 2.4 Tree Photosynthesis and Respiration. 2.5 Primary Productivity. 2.6 Life in the Canopy and Root Epibionts -- 3. Water and Sediment Dynamics. 3.1 Introduction. 3.2 Tides. 3.3 Groundwater. 3.4 Waves. 3.5 Sediment Transport and Flocculation. 3.6 Sedimentation and Accretion. 3.7 Chemical and Biological Consequences of Water and Sediment Flow -- 4. Life in Tidal Waters. 4.1 Introduction. 4.2 Physicochemical and Biochemical Attributes. 4.3 Loops, Chains, and Hubs in the Microbial Machinery. 4.4 Phytoplankton Dynamics. 4.5 Are Mangrove Waters Net Heterotrophic or Autotrophic? 4.6 Zooplankton. 4.7 Nekton. 4.8 Is There a Link between Mangroves and Fisheries Production?- 5. The Forest Floor. 5.1 Introduction. 5.2 Soil Composition and Physicochemical Attributes. 5.3 Life on the Forest Floor. 5.4 Microbial Processes in Forest Soils -- 6. Ecosystem Dynamics -- 7. Synthesis.
Keywords: LIFE SCIENCES; ECOLOGY; ENDANGERED ECOSYSTEMS; AQUATIC BIOLOGY; FORESTS AND FORESTRY; LIFE SCIENCES; ECOLOGY; ECOSYSTEMS; FRESHWATER & MARINE ECOLOGY; FORESTRY